2014
DOI: 10.1063/1.4895783
|View full text |Cite
|
Sign up to set email alerts
|

Height stabilization of GaSb/GaAs quantum dots by Al-rich capping

Abstract: GaSb quantum dots (QDs) in a GaAs matrix are investigated with cross-sectional scanning tunneling microscopy (X-STM) and photoluminescence (PL). We observe that Al-rich capping materials prevent destabilization of the nanostructures during the capping stage of the molecular beam epitaxy (MBE) growth process and thus preserves the QD height. However, the strain induced by the absence of destabilization causes many structural defects to appear around the preserved QDs. These defects originate from misfit disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recently, Smakman et al investigated the defect formation in GaSb/ GaAs QDs with cross-sectional scanning tunneling microscopy. 39) They fabricated GaSb QDs on GaAs and capped them with GaAs, AlAs, or AlGaAs, where the QD height and concentration were 4 « 1 nm and 5 © 10 10 cm ¹2 , respec- tively. They found that the strain in GaSb/GaAs QDs caused many structural defects around the QD, and the defects extended into the capping layer as stacking faults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Smakman et al investigated the defect formation in GaSb/ GaAs QDs with cross-sectional scanning tunneling microscopy. 39) They fabricated GaSb QDs on GaAs and capped them with GaAs, AlAs, or AlGaAs, where the QD height and concentration were 4 « 1 nm and 5 © 10 10 cm ¹2 , respec- tively. They found that the strain in GaSb/GaAs QDs caused many structural defects around the QD, and the defects extended into the capping layer as stacking faults.…”
Section: Discussionmentioning
confidence: 99%
“…The defects were present in 11% of the QDs for GaAs capping, 9-17% of the QDs for AlAs capping, and 22% of the QDs for AlGaAs capping. The defect rate will be reduced for smaller QDs 39) or by annealing processes. 40) The effects of these defects should be considered in the calculation to perform a quantitative evaluation, although our model qualitatively describes GaSb/GaAs QD systems with a relatively low defect rate.…”
Section: Discussionmentioning
confidence: 99%
“…The critical thickness or critical strain is a function of composition of the epitaxial layer. The strain relaxation can also lead to the formation of crystal defects, which strongly affect the optoelectronic properties of the QDs [ 30 , 31 , 32 , 33 ]. Developments in the growth techniques such as MBE or MOVPE in combination with decades of growth optimization made it possible to realize (nearly) defect free QDs.…”
Section: Self-assembled Iii-v Semiconductor Quantum Dotsmentioning
confidence: 99%
“…The size control of DEQDs can also be obtained through engineering the capping layer. This method of optimizing QDs structure was first demonstrated in strained SKQDs, by changing capping layer composition [ 31 , 98 , 99 , 100 ], capping rate [ 101 ], strain field [ 20 ], adding growth interruptions and annealing steps [ 102 , 103 ]. Such a capping process (flushing technique) can be applied to GaAs/AlGaAs DEQDs to obtain a precise control over QDs height.…”
Section: Strain-free Gaas/algaas Deqdsmentioning
confidence: 99%
“…is has been attributed to crystal defects at the QDs' bases, which lead to mismatch dislocations, which dislocate the whole QDs by 1 ML [19]. e resulting stress/strain cannot relax, especially in the case of Al-rich surrounding material.…”
Section: Introductionmentioning
confidence: 99%